Daily social interactions and well-being in older adults: The role of interaction modality. (December 2021) - Macdonald, Birthe; Luo, Minxia; Hülür, Gizem
Associations between social relationships and well-being are widely documented across the lifespan, including in older age. Older adults increasingly use digital communication technologies. In the present study, we examine the role of social interactions for older adults' daily well-being with a focus on three interaction modalities (face-to-face, telephone, and digital). Specifically, we examine (a) whether people who are more socially active than others report higher levels of well-being and (b) how day-to-day fluctuations in the number of social interactions are associated with day-to-day fluctuations of well-being, separately by interaction modality. We use data from 115 participants (age: M = 72 years, SD = 5, range = 65–94; 40% women), who documented their social interactions over 21 days and reported their well-being each evening (including positive affect, negative affect, and loneliness). Taken together, our findings show that frequency of face-to-face interactions is more consistently related to well-being than telephone or digital interactions. At the between-person level, those who report more face-to-face social interactions than others across 21 days report higher levels of positive affect than others. At the within-person level, on days where participants report more face-to-face social interactions than their own average, they report higher positive affect, lower negative affect, and lower loneliness than usual. In addition, a higher number of digital interactions is associated with lower negative affect at the between-person level. In summary, our findings suggest that face-to-face social interactions are uniquely relevant to older adults' daily well-being. We discuss implications of these findings for future research.